Comparison of Two Thrombin Generation Methods, CAT and ST-Genesia, in Liver Transplant Patients - Roullet, Stéphanie; Labrouche, Sylvie; Freyburger, Geneviève (Thrombosis and Haemostasis, 2019)
Background During liver transplantation (LT), thrombin generation (TG) is altered. The most frequently used assay for TG is the Calibrated Automated Thrombogram (CAT). It is designed for series of plasmas and is semi-automated. Complete automation has led to a new device, the ST-Genesia, enabling quantitative standardized TG evaluation.Objective The aim of this observational study was to compare the TG results of the CAT and the ST-Genesia on frozen-thawed plasma samples prepared from the blood of LT patients.Patients and Methods Poor platelet plasma aliquots were prepared from blood samples from six LT patients selected to get the whole range of TG and were assessed with CAT (recombinant human tissue factor [TF] concentration 5 pm) and with ST-Genesia Bleedscreen assay (BS, using ‘low’ recombinant human TF concentration) and Thromboscreen assay (TS, using ‘medium’ recombinant human TF concentration). The TG parameters studied were: lag time, peak, time to peak, endogenous thrombin potential, velocity index and start tail.Results BS and TS did not differ significantly from each other whatever the parameter studied, whereas most of the CAT parameters were significantly different from those obtained with BS and TS. Hierarchical clustering analysis of the different parameters of TG showed three homogeneous groups. One cluster gathered TG quantitative parameters from ST-Genesia. A second cluster gathered all the kinetic parameters. The last cluster isolated the quantitative parameters of CAT.Conclusion In patients undergoing LT, TG performed with CAT and with ST-Genesia provided different results, for unknown reasons.
Keywords: blood coagulation; cluster analysis; device; liver transplantation; thrombin